Internal Audit Practice in Malaysian Public Sector Organizations - Nur Ain Zakiah, Mohd Yusof; Hasnah, Haron; Ishak, Ismail (Universiti Malaysia Pahang, 2016)
This descriptive paper provides an overview of the Malaysian public sector structure and the internal audit in its organization. Malaysian public sector is unique in terms of its governmental system which is a combination of federalism, democracy and monarchy. The structure of public sector organization in Malaysia comprises of several level and types of organizations which lead to the complexity of the structure thus requires a comprehensive procedure and guidelines especially in financial management. Internal audit practice in Malaysia has evolved since 1970 and its role is expanding through the requirement and instruction from Treasury Malaysia. Nevertheless, there are still a lot of issues concerning internal audit function and its effectiveness arises in Malaysian public sector. Comprehensive studies on this matter are highly recommended.